2007
DOI: 10.5713/ajas.2007.340
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-activated Receptor ??Is Involved in Weaning to Estrus of Primiparous Sows by Regulating the Expression of Hormone Genes in Hypothalamus-pituitary-ovary Axis

Abstract: The objective of this study was to determine whether peroxisome proliferator-activated receptor γ (PPARγ) is involved in the regulation of weaning to estrus of primiparous sows. Twelve sows composed of 6 groups of 2 full-sibs in a similar age (325.2 d), body weight (BW; 152.4 kg) and backfat thickness (BFT; 27.0 mm) at start of lactation, were allocated to accept 31 MJ (restricted group, R-group) or 53 MJ (control group, C-group) DE/d treatment, respectively. The experimental results indicated that the low ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Lactating sows fed high density diet in the hot environment had a tendency for elevated levels of plasma LH compared with sows lactating in ST. Increasing LH secretion and follicular growth may have contributed to feed intake, since energy received through feeding has a significant effect on increasing LH [ 31 ]. The reduced LH secretion at elevated temperatures decreases follicle growth in lactation period and restrict follicle development after lactation [ 8 ]. Our study showed an insignificant effect of energy levels on weaning to estrus interval, whereby the sows fed high energy tended to have a greater blood LH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactating sows fed high density diet in the hot environment had a tendency for elevated levels of plasma LH compared with sows lactating in ST. Increasing LH secretion and follicular growth may have contributed to feed intake, since energy received through feeding has a significant effect on increasing LH [ 31 ]. The reduced LH secretion at elevated temperatures decreases follicle growth in lactation period and restrict follicle development after lactation [ 8 ]. Our study showed an insignificant effect of energy levels on weaning to estrus interval, whereby the sows fed high energy tended to have a greater blood LH.…”
Section: Discussionmentioning
confidence: 99%
“…The subsequent parity also can be affected by amplifying the inhibition of gonadotrophin releasing hormone and luteinizing hormone (LH) secretion in lactation, which prolongs the WEI [ 8 ]. In a previous study on the interaction between reproductive performance and heat stress in sows, the number of embryonic mortality significantly increased in sows exposed to heat [ 9 ].…”
Section: Introductionmentioning
confidence: 99%